Rancang Bangun Sistem Aplikasi Inventory Barang Berbasis Web (Studi kasus: PT. Batam Bintan Telekomunikasi) - Muhammad Abizar Rafliansyah; Surtikanti (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
PT Batam Bintan Telekomunikasi is a company engaged in telecommunications and network services that operates specifically in the Mukakuning industrial area of ​​Batam island, Lobam industrial area and Lagoi resort area on Bintan island. Problems occur when there are many items whose device identity data are unknown at the company, causing a long search for identity device data, especially network devices that still do not reserve their quantity and usage for any activity, which makes the inventory system unstructured and not good enough. Currently, data reports on items that have been used and reports on backups of owned devices are also not available. So that when data is needed, data reports cannot be accessed directly. In the method of designing this inventory system application using the waterfall model. Based on the problems above, a website will be designed for an inventory application that can make it easier to control the existing equipment quickly and accurately at this company. With the existence of a website for inventory of goods that will be made, it is hoped that it can help record network equipment infrastructure that has been used, record inventory results reports automatically and of course it is hoped that it can reduce problems that often occur.